KINERJA PELAYANAN BADAN PERTAHANAN NASIONAL - Putri Vara Dina (Universitas Riau, 2015)
Service Performance National Land Agency. Study is to examine the performance of the services provided by the Land Office Pekanbaru in making land titles and become factors inhibiting. The informants in this study was the leader BPN Pekanbaru, executive coordinator, community service providers and service recipients. Data collecting technique is interview, documentation and observation. Data were analyzed using descriptive models ranging from interactive data reduction, data display and conclusion. Based on the survey results revealed that the BPN service performance in providing services to the community in the service of granting land rights to individuals, legal entities of private and religious social institutions remains low, limited personnel, the completeness of the maintenance requirements of land titles and land in trouble